The dynamics of leadership on innovative behavior: A study of Indonesia’s non-metallic minerals industry - Kamal Aldi Bin Syamsul; Putri Icut Pridani; Maharani Anita (Journal of Economics and Management)
Aim/purpose – The purpose of this paper is to investigate the impact of transformational leadership (TL) on innovative work behavior (IWB) among middle management in the non-metallic mineral products industry, focusing on job crafting (JC) and knowledge-sharing behavior (KSB) as mediating factors.